An analysis of perioperative outcomes following cervical abscess drainage in children under 2 years. (January 2019) - Harounian, Jonathan A.; Patel, Vijay A.; Carr, Michele M.
Abstract: Objective: To identify risk factors and determine perioperative morbidity of children under 2 years of age undergoing cervical abscess drainage. Methods: Patients who underwent cervical abscess drainage 1–18 years of age were queried via the ACS-National Surgical Quality Improvement Program-Pediatric (NSQIP-P) database (2012–2015). Analyzed outcomes include length of stay, operative time, readmission/reoperation rate, and postoperative complications. Results: A total of 2181 children were identified, 858 were <2 (51.5% male) and 1323 were >2 years (57.1% male) (p = 0.011). The younger cohort was found to undergo more lateral approaches for cervical abscess drainage whereas the older cohort was found to undergo more intraoral approaches for pharyngeal abscess drainage (p < 0.001), suggesting a difference in abscess location related to age at clinical presentation. The younger cohort was also found to have a higher preoperative white blood cell count (20.7 vs. 17.5, p < 0.001) but no significant difference in preoperative fulminant sepsis was observed. Younger children were found to have both a longer wait-time until surgery (1.4 vs. 1.1 days, p = 0.003) and a prolonged length of stay (LOS) (4.3 vs. 3.4 days, p < 0.001). Operative time was found to be lower in the younger cohort (18.4 vs. 21.5 min, p = 0.003), Finally, the younger cohort was found to have an increased incidence and duration of postoperative mechanical ventilation (63 vs. 41, and 0.4 vs. 0.1 days, respectively, p < 0.001.). There were no differences in post-op complications (wound infection, dehiscence, pneumonia, reintubation, and reoperation/readmission). Linear regression for LOS showed that major contributors were operative time, days of postop ventilation, and days from admission to surgery with R = 0.700. Conclusion: Children under 2 years of age have longer LOS that may in part be due to a greater likelihood of postoperative ventilation and a delay in operative intervention, despite having surgical approaches associated with a shorter LOS. They are no more prone to complications than are older children. Recognition of these critical factors plays a role in optimizing perioperative risk assessment and procedural planning within this patient population.